Adrenomedullin in patients with type 2 diabetes and kidney disease - Waked, Emam; El Bendary, Omnia; Metwaly, Amna; Younes, Khaled; Assal, Heba Sayed; Sayed, Hanan Ali (African Journal of Nephrology, 2009)
<p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Secreting vasoactive factors such asadrenomedullin (AM) has been intensivelyinvestigated due to its vascular protective propertiesand promising potential as a therapeutic target. Therelationship between adrenomedullin and type (2)diabetes needs to be elucidated as it is associatedwith significant elevation in plasma adrenomedullinlevels. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">The aim of this study was to evaluate therole of adrenomedullin in the development ofvasculopathy and its significance as a markerdenoting renal affection in type 2 diabetic patients. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Materials and Methods: This study was conductedon 60 diabetic patients, 20 without nephropathy, 20with nephropathy & 20 with diabetic nephropathy(DN) on haemodialysis as well as 20 age- and sex matchedhealthy controls. All were subjected to fullhistory, Echocardiography, lipid profile analysisand plasma adrenomedullin using ELISA method. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: plasma AM concentration was elevated inall groups of diabetic patients and increment wasdependent on the severity of DN (P<0.0001,P<0.0001, P<0.0001 respectively). There werepositive correlation between adrenomedullin andleft ventricular internal dimensions both in diastole& systole (P<0.001, P<0.005) and negativecorrelation between AM and ejection fraction (EF)P<0.0001. There was positive correlation betweenadrenomedullin and cholesterol, triglycerides andLDL (p<0.002, p<0.001and p<0.003 respectively)and a negative correlation with HDL (P<0.004). <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: Adrenomedullin is supposed to play arole in the pathogenesis of diabeticmicrovasculopathy in renal patients. So it can beused to identify high-risk subjects and modulatingits action would have therapeutic potential in the prevention of diabetic nephropathy.